The relationship between land administration systems and spatial change in peri-urban areas in Ghana: the case of Kumasi and Sunyani - Anane, George Kwadwo (My University, 2022)
Peri-urban areas in Ghana are experiencing rapid spatial transformation. Contributing to existing literature on African peri-urbanisation, this thesis examines the emerging spatial and structural changes in peri-urban settlements, the roles and conflictual relationship between statutory and traditional authorities in peri-urban governance in Ghana, and the impact they exert on peri-urbanisation. The thesis adopted the case study strategy focusing on rapidly growing peri-urban municipalities of Abuakwa and Adomako, peripheral to Kumasi and Sunyani, respectively, which represent customary and statutory land tenure systems typical of Ghana. This qualitative paradigm was used to survey changing physical spaces as well as to analyse emerging forms of actor relationships that impact such changes. Here, the conflictual relationships between centrally placed actors engaged in tenure, land administration practices, and peripheral actors become particularly relevant. Two cases were purposively selected. Case studies were constructed through the qualitative paradigm, maps, and interviews that solicited the views and experiences of different actors in peri-urban development. The study involved the use of secondary data such as official documents, Landsat data, drawings, and core-periphery analysis. This was supplemented by empirical data from field visits and in-depth interviews conducted with 26 knowledge-rich respondents in the two case studies from 2018 to 2019. The respondents were planners, chiefs, and peri-urban developers in Abuakwa and Adomako. Both cases revealed that despite their differences, traditional and statutory authorities have formed pragmatic alliances that recognise each party as a significant stakeholder in land administration and land use planning. The analysis also discovered that this was different in the past, revealing a new trend. This emerging trend in the role of traditional and statutory authorities is relevant because it has developed conflict resolution capacity to better deal with the differences that arise from land ‘ownership’, and land administration and land use planning. The underlying thrust of the pragmatic alliances is that both traditional authorities and statutory officials concentrate on short-term spatial change decisions, mainly in the preparation of local plans and the transfer of land. As a result, less attention is given to critical dimensions of peri-urban transformation such asthe social, environmental, infrastructural, and spatial aspects, which require long-term thinking and planning. This increases the propensity to produce ambivalent transformation outcomes, involving favourable and unfavourable environmental, economic, and socio-spatial consequences in peri-urban areas.
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy in Urban and Regional Planning, 2022